RePair: (im)possibilities of care-taking and making with care in times of isolation - Friess, Carola (Michaelis School of Fine Art, 2022)
The sudden and drastic impacts the recent global health crisis had on my life, and on society more broadly, triggered intuitive processes of creation, whereby its context was difficult to grasp in the beginning. Thus, my motivation for conducting this research stemmed from a personal worry about the dystopian situation outside of my private sphere. The many social upheavals caused by the pandemic would ultimately shape my thinking through creative production. This allowed me to grasp the many intangible aspects of my life and my conception of the world in a productive way; and connect many disparate aspects through a process of corporeal engagement that, literally and figuratively, stitched emotional and conceptual ruptures together as can be observed in the art objects displayed in the exhibition. This body of work thus explores the complexity of the act of repairing as a frame for art-making: as a means to articulate strategies of care in times of isolation, with the full knowledge of an indefinite outcome that does not sully the endeavour. My former profession as a surgical nurse, a profession of collective care-taking, and profiled as an ‘essential worker' during this pandemic, has had a substantial impact on this project. My specific interest is the transition from an act of care-taking for a stranger into artistic processes in isolation, that nevertheless involves a manner of care despite important differences. The times of social separation made me realise how interconnected we are. Thus, RePair is an attempt to emphasise the importance of relational perspectives wrought from the two subject positions I inhabited as a nurse and as an artist. I consider this document in conjunction with the body of artworks displayed as a means to explore the transformative potential of a relational and affective set of aesthetic considerations in a time of a shared crisis.